2019
DOI: 10.1007/s41959-019-00019-y
|View full text |Cite
|
Sign up to set email alerts
|

Three keys to entrepreneurial success: curiosity, creativity, and commitment

Abstract: Why are some entrepreneurs more successful than others? This question is foundational to entrepreneurial education but answers remain elusive. It is argued here that three Cs in part hold the key: curiosity, creativity, and commitment. The world's most successful entrepreneurs are curious about improving society, they are creative in developing innovative ideas, and they are committed to their task. This commentary develops an initial model of how basic personality traits lead to these three core characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…The characteristics that were most often mentioned by respondents during their interviews and after participating in each of the IWLs were creativity, teamwork, openmindedness, innovation and passion, in line with authors such as Keyhani and Kim (2020); Raine and Pandya (2019) and Syae (2020). The characteristics that the participants repeated every time they were asked, in addition to the previous ones, included motivation, hard work, risk-taking, ability to deal with challenges, taking the initiative, proactivity, organisation skills, perseverance, and leadership and communication skills, as well as an ability to adapt, be positive and make decisions.…”
Section: Discussionmentioning
confidence: 80%
“…The characteristics that were most often mentioned by respondents during their interviews and after participating in each of the IWLs were creativity, teamwork, openmindedness, innovation and passion, in line with authors such as Keyhani and Kim (2020); Raine and Pandya (2019) and Syae (2020). The characteristics that the participants repeated every time they were asked, in addition to the previous ones, included motivation, hard work, risk-taking, ability to deal with challenges, taking the initiative, proactivity, organisation skills, perseverance, and leadership and communication skills, as well as an ability to adapt, be positive and make decisions.…”
Section: Discussionmentioning
confidence: 80%
“…Employees have competences related to teamwork skills in connection with creativity, commitment and entrepreneurship confirms a positive impact on the development of the company (Raine and Pandya, 2019;Daniel and Almeida, 2020). A positive aspect resulting from the ability to work in a group is also the ability to resolve conflicts and achieve job satisfaction (De Dreu and Van Vianen, 2001), which is an important factor in the sustainability of employment.…”
Section: Teamwork As An Important Factor Of Managers' Competencesmentioning
confidence: 95%
“…During a study, Jeraj (2014) hypothesized optimism as a variable that positively influences preentrepreneurial curiosity. Since Raine and Pandya (2019) have also affirmed optimism as a highly associated variable with entrepreneurial curiosity, the current study's researchers identified pre-entrepreneurial curiosity as a valid construct that can use with optimism to evaluate students' entrepreneurial intentions.…”
Section: Pre-entrepreneurial Curiositymentioning
confidence: 96%